Levinasian Ethics of Face as Moral Guidance for Leaders of Superior Quality - Agustinus Tamtama Putra; Along, Antonius (Dekonstruksi, 2025)
This paper elaborates on Emmanuel Levinas' idea of the face of the other, which is the ethical basis for the most humane treatment of others as subjects. This idea of the ethics of the face of levinasian then becomes a moral guideline for leaders of superior quality. The author argues that a good leader is one who sees and treats anyone not as an object, let alone as a means to get personal gain. An excellent leader is one who first realises that other people are the most prioritised, upheld in dignity, loved as the primordial human intuition in looking at someone's face. In conclusion, this research underlines the discovery that superior quality leaders are effectively formed through the meaning and embodiment of levinasian face ethics in various contexts of life together.